2011
DOI: 10.1111/j.1442-2018.2011.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Sudden cardiac death: the perspectives of Spanish survivors

Abstract: Sudden cardiac death is an episode of sudden death from cardiac causes in previously healthy patients. The aim of this study was to investigate the life experiences of patients who were resuscitated successfully following a sudden cardiac death. Purposeful sampling was used to recruit the nine participants through the snowball technique. Unstructured interviews were carried out until data saturation was reached. The Giorgi method of analysis, which seeks to reduce the participant's experience to minimal themat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 31 publications
(56 reference statements)
2
45
0
Order By: Relevance
“…With the act of placing the family first, concern for family members' experience and their need for support arose. Similar results have been reported in previous studies, 12,13,26,28 in which participants expressed gratitude for being alive, developed a new perspective on life and learned to live again.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…With the act of placing the family first, concern for family members' experience and their need for support arose. Similar results have been reported in previous studies, 12,13,26,28 in which participants expressed gratitude for being alive, developed a new perspective on life and learned to live again.…”
Section: Discussionsupporting
confidence: 91%
“…In a Swedish study 12 as well as in a Spanish study, 13 both including nine SCA survivors, the findings show how the cardiac arrest suddenly changes their lives. The survivors do not have a clear understanding of what has happened or its meaning.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…This is in keeping with the review by Wilder Schaaf and colleagues, 11 and qualitative research, which demonstrate a particularly high prevalence of anxiety compared with depression. 20 Indeed, informal feedback from patients suggested that the difficulty of recovering emotionally from their experience far exceeded any physical challenge of rehabilitation. A higher mean level of anxiety despite a normal level of depression and stress suggests that using non-specific measures could omit individuals in need of psychological support.…”
Section: Discussionmentioning
confidence: 99%
“…Others had not received enough information, had received contradictory information or did not receive answers to their questions in time and therefore needed to ask questions. Palacios‐Cena, Losa‐Iglesias, Salvadores‐Fuentes, and Fernandez‐de‐las‐Penas (), in another study that did not specify whether the cardiac arrest occurred in or outside hospital, showed that the patients were afraid that it could happen again, which affected various aspects of their lives. They searched for a reason for what had happened but received no clear answers and felt frustration.…”
Section: Introductionmentioning
confidence: 99%